Efficacy of Suprachoroidal Triamcinolone Acetonide Injections in Resistant Diabetic Macular Edema: Suprachoroidal Triamcinolone Acetonide in Resistant Diabetic Macular Edema - Kumar, Vijay; Memon, Nasir Ahmed; Haseeb, Uzma; Kazi, Umer; Shah, Shahid Hussain; Qadeem, Abdul (Pakistan Journal of Health Sciences, 2025)
Localized drug delivery through the suprachoroidal space can be used for more targeted therapies whilst minimize exposure to the healthy tissues. Objectives: To determine the efficacy of suprachoroidal triamcinolone injection given by the suprachoroidal route in patients with resistant diabetic macular edema. Methods: A quasi-experimental study was done at Al Ibrahim Eye Hospital, Karachi’s Vitreo-retina Department. Duration of research was 6 months (July to December 2024) (ATMC/ERC/13 (01/2023/22). Adult patients attending the vitreo-retinal OPD with resistant diabetic macular edema were included. Data were analyzed using SPSS version 22.0. Discrete variables were reported as mean and standard deviation, and continuous variables as frequencies and percentages. BCVA and CST readings at 4, 8 and 12 weeks were compared with baseline using a paired t-test, with p-value <0.05 statistically significant. Results: Before injection. The pre- and post SCTA BCVA and CST with baseline mean BCVA were 1.1 ± 0.30, which progressively improved at subsequent follow-ups, reaching 0.33 ± 0.18 by the third month post-injection. Conclusions: SCTA injections significantly improve visual acuity and reduce central subfield thickness in patients over a three-month follow-up period. The progressive enhancement in Best Corrected Visual Acuity and consistent reduction in Central Subfield Thickness highlight the efficacy of SCTA